Promoting electrochemical ammonia synthesis by synergized performances of Mo2C-Mo2N heterostructure - An, Tae-Yong; Surendran, Subramani; Jesudass, Sebastian Cyril; Lee, Hyunjung; Moon, Dae Jun; Kim, Jung Kyu; Sim, Uk (Frontiers in Chemistry, 2023)
Hydrogen has become an indispensable aspect of sustainable energy resources due to depleting fossil fuels and increasing pollution. Since hydrogen storage and transport is a major hindrance to expanding its applicability, green ammonia produced by electrochemical method is sourced as an efficient hydrogen carrier. Several heterostructured electrocatalysts are designed to achieve significantly higher electrocatalytic nitrogen reduction (NRR) activity for electrochemical ammonia production. In this study, we controlled the NRR performances of Mo2C-Mo2N heterostructure electrocatalyst prepared by a simple one pot synthesis method. The prepared Mo2C-Mo2N heterostructure nanocomposites show clear phase formation for Mo2C and Mo2N, respectively. The prepared Mo2C-Mo2N electrocatalysts deliver a maximum ammonia yield of about 9.6 μg h-1 cm-2 and an FE of about 10.15%. The study reveals the improved NRR performances of Mo2C-Mo2N electrocatalysts due to the combined activity of the Mo2C and Mo2N phases. In addition, the ammonia production from Mo2C-Mo2N electrocatalysts is intended by the associative NRR mechanism on Mo2C phase and by Mars-van-Krevelen mechanism on Mo2N phase, respectively. This study suggests the importance of precisely tuning the electrocatalyst by heterostructure strategy to substantially achieve higher NRR electrocatalytic activity.